Life Satisfaction, Self-awareness and Personal Responsibility in Seminary Students - Lio, Stefanus; Degeng, I Nyoman Sudana; Hambali, IM; Hitipeuw, Imanuel (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study investigated the associations among life satisfaction, self-awareness, and personal responsibility. It also examined whether life satisfaction, self-awareness, and personal responsibility vary according to the year of study. The respondents were 36 students at the Seminary of Surya Wacana in Malang. For data collection, the Self- Consciousness Scale, Personal Responsibility Scale, and Satisfaction with Life Scale were used. Pearson correlation coefficient results showed that life satisfaction was significantly positively correlated with self-awareness (r = .454, p < .05), but not to personal responsibility (r = .002, p > .05). Multiple regression analysis revealed that self-awareness and personal responsibility accounted for 25.1 % of life satisfaction (F= 5.522, p < .05). Self-awareness (ß = .554, p < .05) and personal responsibility (ß = -.234, p > .05) simultaneously make a significant original contribution to the model. In addition, results showed that seminarians do not vary according to year of study in terms of self-awareness (F = 1.217; p > .05), personal responsibility (F = .980; p > .05), or life satisfaction (F = .631; p > .05). The study results showed that self-awareness and personal responsibility are significant predictors of life satisfaction in seminary students.